"Emotional intelligence and academic self-efficacy as predictors of academic performance among senior secondary school students in Oyo state, Nigeria " (2009)
"This study examined the predictive effects of emotional intelligence and academic self-efficacy on academic performance of students. The study adopted a survey research design of an ex-post facto type. Participants were 485 secondary school students randomly selected from ten co-educational secondary schools in Oyo State (male=258; female=226). The research instruments used for data collection were: Emotional Intelligence Behaviour Inventory (EOBI, a = 0.88), Academic Self-Efficacy Scale (ASES, a = 0.82), English Language Achievement Test (ELAT, a = .76) and Mathematics Achievement Test (MAT, a = .79) tested at the 0.05 level of significance. The findings indicated that emotional intelligence and academic self-efficacy were potent predictors of academic performance of students. "